2006
DOI: 10.1007/s00125-006-0469-z
|View full text |Cite
|
Sign up to set email alerts
|

Ethnicity modifies the association between diabetes mellitus and ischaemic heart disease in Chinese, Malays and Asian Indians living in Singapore

Abstract: Aims/hypothesis The aim of the study was to determine whether the risk of ischaemic heart disease (IHD) associated with diabetes mellitus differs between ethnic groups. Methods Registry linkage was used to identify IHD events in 5707 Chinese, Malay and Asian Indian participants from three cross-sectional studies conducted in Singapore between the years 1984 and 1995. The study provided a median of 10.2 years of follow-up with 240 IHD events experienced. We assessed the interaction between diabetes mellitus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 41 publications
2
53
1
1
Order By: Relevance
“…The ethnic differences in the association between diabetes mellitus and ischemic heart disease are noted even within Asian populations. 3 In Asian countries, as a consequence of the economic developments, the prevalence of overweight and obesity is increasing, and more important, rates of diabetes are increasing even more quickly. In particular, a moderate increase in body mass index makes South Asians more prone to insulin resistance and related diseases.…”
Section: Risk Factors Of Cardiovascular Diseasesmentioning
confidence: 99%
“…The ethnic differences in the association between diabetes mellitus and ischemic heart disease are noted even within Asian populations. 3 In Asian countries, as a consequence of the economic developments, the prevalence of overweight and obesity is increasing, and more important, rates of diabetes are increasing even more quickly. In particular, a moderate increase in body mass index makes South Asians more prone to insulin resistance and related diseases.…”
Section: Risk Factors Of Cardiovascular Diseasesmentioning
confidence: 99%
“…This is especially true in view of the effectiveness in reducing lipid levels in this group of patients [9]. There have been numerous studies demonstrating the lipid lowering effects of statin in various patient populations [2,4]. However, its effects have been notably varied with interindividual differences [2].…”
Section: Discussionmentioning
confidence: 99%
“…It is also the leading cause of death in Malaysia, accounting for 2,556 deaths in 2002 [2]. Several risk factors have been identified that increases the likelihood of IHD.…”
Section: Introductionmentioning
confidence: 99%
“…In a 10-year prospective observational study that involved 5,707 participants of Chinese, Malay and Asian Indian participants from 3 cross-sectional studies conducted in Singapore, Yeo KK et al showed that ethnicity modified the risk of CHD associated with diabetes mellitus 33) . They showed that over and above the increased baseline risk of CHD, diabetes mellitus had a larger effect on the risk of CHD in Asian Indians than in Chinese and Malays 33) . The population attributable risk of CHD related to diabetes mellitus was 40.9% in Asian Indians compared with 27.9% in Malays and 11.0% in Chinese.…”
Section: Discussionmentioning
confidence: 99%